Chrysanthemum - Henkes, Kevin (New York : Scholastic, 1991)
Chrysanthemum loves her name, until she starts going to school and the other children make fun of it.
Originally published; New York; Greenwillow Books, 1991
"This edition is only avilable for distribution through the school market." --cover, p. 4
Keywords: Names, Personal -- Fiction; Schools -- Fiction